Empowering Educators, Supporting Students: A Quasi-Experimental Evaluation of a Train-the-Trainer Model for School Mental Health in Indonesia - Ahmad Badruddin; Omar Alieva; Ifah Shandy; Henny Kesuma; Benyamin Wongso; Winata Putri; Habiburrahman Said (HM Publisher, 2025)
Adolescent mental health is a pressing concern in urban Indonesian schools, where a significant gap exists between student needs and the availability of professional support. This study evaluated the efficacy of a culturally-adapted, school-based